Association between guidelines and medical practitioners' perception of best management for patients attending with an apparently uncomplicated acute sore throat: a cross-sectional survey in five countries. Issue 9 (17th September 2020) - Gunnarsson, Ronny; Ebell, Mark H; Wächtler, Hannelore; Manchal, Naveen; Reid, Lynne; Malmberg, Stefan; Hawkey, Sean; Hay, Alastair D; Hedin, Katarina; Sundvall, Pär-Daniel
Abstract : Objective: To investigate the relationship between guidelines and the medical practitioners' perception of optimal care for patients attending with an apparently uncomplicated acute sore throat in five countries (Australia, Germany, Sweden, UK and USA). Design: International cross-sectional survey. Setting: Primary healthcare (PHC). Participants: Medical practitioners working in PHC. Main outcome measures: ORs for: (A) perception of throat swabs as important, (B) perception of blood tests (C reactive protein, B-ESR and B-leucocytes) as important and (C) antibiotic prescriptions if no pathogenic bacteria isolated on throat swab. Results: Guidelines differed significantly; those recommending throat swabs (Sweden and USA) were associated with practitioners perceiving them as important. The UK guideline was the only one actively discouraging the use of throat swabs. Hence, compared with the USA (reference), a throat swab showing no pathogenic bacteria increased the probability of antibiotic prescribing in the UK with OR 3.2 (95% CI 1.7 to 6.1) for adults, whereas it reduced the probability in Sweden for adults OR 0.35 (95% CI 0.13 to 0.96) and children 0.19 (95% CI 0.069 to 0.50). Conclusions: The differences between practitioners' perceptions of best management were associated with their guidelines. It remains unclear if guidelines influenced medical practitioners' perception or if guidelines merely reflect the consensus of current practice. A larger effort should be made to reach an international consensus in high-income countries about the best management of patients attending for an uncomplicated acute sore throat.